Intraoperatory Choledocoscopy - Bermúdez, Jorge (Cirugía del Uruguay, 1980)
A primary intraoperatory experience with a rigid choledocoscope is reported. The high rate of residual calculi overlooked by convent.ional methods ( 42 % ) and 25,7 % of intrahepatic stones are pointed out.